4-Methylesculetin ameliorates LPS-induced depression-like behavior through the inhibition of NLRP3 inflammasome - Khushboo Choudhary; Surendra Rajit Prasad; Kiran Bharat Lokhande; Krishna Murti; Sanjiv Singh; Velayutham Ravichandiran; Velayutham Ravichandiran; Velayutham Ravichandiran; Nitesh Kumar (Frontiers Media S.A., 2023)
The pathophysiology of depression is heavily dependent on inflammation. Evidence suggests that the etiology of depression is linked with NLRP3 inflammasome-induced inflammation. Therefore, blocking the activated NLRP3 inflammasome may be beneficial for treating depression. Due to the limitations of currently available antidepressants, it is necessary to develop novel, safe, and affordable drugs for the treatment of depression. A natural coumarin derivative named 4-methylesculetin (4-MESC) possesses anti-inflammatory properties. However, the role of 4-MESC as an antidepressant has not been elucidated. Therefore, in this study, we explored the antidepressant-like effects of 4-MESC and its underlying molecular mechanism through the modulation of the NLRP3 inflammasome. The docking and molecular dynamic simulation studies revealed that 4-MESC has a higher affinity for the NLRP3 PYD. Blood-brain barrier permeability was confirmed using the SwissADME pharmacokinetic tool. High doses (50 mg/kg) of 4-MESC significantly reduced the immobility duration in the tail-suspension test (TST) and forced swim test (FST) without changing the overall locomotor activity in the female Swiss albino mice that were subjected to lipopolysaccharide (LPS). LPS-induced pro-inflammatory cytokines such as IL-6 and TNF-α were reduced in serum and brain tissues using 4-MESC. 4-MESC's neuroprotective effects are mediated by increased brain-derived neurotrophic factor (BDNF) and decreased cortisol levels. 4-MESC markedly reduced LPS-induced elevated levels of ROS and lipid peroxidation (malondialdehyde levels) and enhanced the superoxide dismutase (SOD) activity and glutathione levels, which revealed its anti-oxidant potential against oxidative stress. 4-MESC diminished the expression levels of NF-κBp65, IL-6, NLRP3, caspase-1, gasdermin D, and IL-1β in the hippocampus. These findings demonstrated that 4-MESC exhibited antidepressant-like effects by inhibiting the NLRP3 inflammasome. However, other antidepressant mechanisms might also be involved which require further studies.